"Reforma urbana já"; "arroz, feijão, saúde e habitação" :A luta por moradia na grande João Pessoa - Dowling, Gabriela Buonfiglio (2006)
Our object of study in this work concerns to the movement of fight for the housing in the Great João Pessoa, Paraíba, Brazil, and looks for to investigate the conditions and context of the occupations of building, public or private, for devoid populations that do not have where to live. Front to the absence of politics effective directed to the habitation or the cities, in a picture of unemployment and impoverishment of the population, the result of the habitation point of view, is the absolute lack of popular housings, the degradation of the cities and the growth of the number of homeless and also of its occupations. The urban occupations today represent a reply of these devoid populations that from an involvement with parties or Not Governmental Organizations, and social movements leave for the class action known by the occupation of abandoning public or private buildings. These occupations, even so initially if assume as pressure instrument or of visibility for attainment of housings, for the delay in obtaining the attention of the public agencies and a solution for the problem, becomes definitive or is drawn out per many years. E this if gives although the deficiencies, of the accumulation or families neither in an adequate, always precarious space nor in sanitary installations, that the necessary privacy does not allow. The study it consisted of an empirical research, through the participant comment and open and half-open interviews, and counted on the audiovisual register of two occupations, one in the downtown of João Pessoa City (old building of the INSS, in the Ponto dos Cem Réis) and other (Community of the Cajueiro), next to the Beach "Praia do Jacaré", in the city of Cabedelo.The choice of the Visual Anthropology as research instrument is on to a concern in better translating other ways of life, therefore the accomplishment of the video in allows them to know with more precision the reality where the citizens of the research live. We also use as methodological resource in the research the deepened interview, in intention to better understand the description of the way of life of the studied families and the movements of fight for the housing, particularly the MDM - Movement of Right for the Housing, and the MNLM- Nacional Movement of Fight for the Housing